Diagnostic Accuracy of Frozen Section in Surgical Diseases with Critical Evaluation of Disconcordant Reports - Anupama Dayal; Rupal J Shah; Dipak Joshi; SM Patel (National Journal of Laboratory Medicine, 2019)
Introduction: The primary work of frozen section is to provide intraoperative rapid diagnosis, essential for patient management. The indications are to determine nature of lesion, margin status and staging of malignant tumours. Aim: To find the accuracy of frozen section as compared to paraffin section. Detailed analysis of discordant cases so as to find the common errors responsible for discrepancy. Suggest ways to improve the overall accuracy of frozen section. Materials and Methods: In this study, results of 172 consecutive cases of frozen sections were compared with the final paraffin section diagnoses in tertiary care, teaching hospital of Gujarat, India, over a period of one year and six months. Data were entered in Microsoft Excel sheet; diagnostic accuracy along with sensitivity and specificity were analysed using Medcalc statistical software, version 13.2, Belgium. Results: Out of 172 cases, two cases were deferred for paraffin section (deferral rate 1.16%). The overall accuracy of frozen section was 95.3%. Amongst the discordant cases, interpretation error was responsible in 50%, block sampling error and specimen sampling error in 25% of cases each. The overall sensitivity and specificity was 93.4% and 98.44% respectively. Conclusion: Frozen section is a reliable, cost-effective and useful technique if its limitations and indications are kept in mind. Detailed gross examination with multiple sections in suspicious malignant cases, broad diagnosis of benign/malignant in case of uncertainty and good interdepartmental communication helps to improve the accuracy.